The Influence Of Organizational Culture And Communication On Work Conflicts Of Employees At Pt.Nagamas Agro Mulia Medan - Melissa Rinata; Syawaluddin; Aidil Putra; Thomas Sumarsan Goh (Institute of Computer Science (IOCS), 2022)
PT. Nagamas Agro Mulia is a company engaged in the processing of palm oil. Phenomena that occur in the company are: the existence of work conflicts between employees, causing disruption to company activities. This problem is allegedly caused by organizational culture and communication. The population in this study were all employees of PT. Nagamas Agro Mulia, totaling 174 employees. This study uses the Slovin Formula, so the number of samples is 121 respondents. This study uses multiple linear regression analysis to get a picture of the relationship between variables. The results of the simultaneous hypothesis test show that simultaneously, organizational culture and communication have a significant effect on work conflict of employees at PT. Nagamas Agro Mulia Medan. Partially, each variable of organizational culture and communication has a significant effect on work conflicts of employees at PT. Nagamas Agro Mulia Medan.